Neoadjuvant Chemo-irradiation in un-resectable Carcinoma of Rectum - Abbas, Asad; Tunio, Mutahir Ali; Ali, Nasir (Journal of Ayub Medical College Abbottabad, 2004)
Background: Rectal cancer is one of the most frequent gastrointestinal cancers. Conventionally surgery is the mainstay of treatment, however after surgery alone, local recurrence is high especially in locally advanced rectal cancer, i.e. tethered and fixed rectal cancer. This study was conducted to determine the role of neo-adjuvant (pre-operative) chemo-irradiation in locally advanced carcinoma of the rectum to improve resectability , local control and survival. Methods: Study was conducted in Radiation Oncology department of Shaukat Khanum Memorial Cancer Hospital and Research Center from May 97-Oct 99. Thirteen patients with unresectable/ locally advanced adenocarcinoma rectum received neo-adjuvant chemoirradiation, 50 Gray to pelvis by box technique on Cobalt-60 machine with concomitant 5-Flurouracil 500mg/m2 for first three and last three days followed by abdomino-perineal /low anterior resection. Results: Neo-adjuvant chemoirradiation resulted in resectability rate of 92% and clinical down staging in 11/13 (84%) patients and pathological complete response in 2/13 (15%) patients and a local recurrence rate of 2/13 (15.38%). Non hematological toxicity (diarrhea grade 4-15%, erythema grade3-23%, dysuria grade1-2-38%) were main problems observed during neo-adjuvant chemoirradition. Conclusion: Concomitant preoperative chemoirradiation for locally advanced rectal cancer is associated with considerable clinical and pathological down staging. Tumor resectability is improved with potential for improved local control and is relatively safe with acceptable morbidity. KEY WORDS: Unresectable rectal cancer, resectibility rate, neo-adjuvant chemoirradiation